Exploring the efficacy of game-based learning models in enhancing children's gross motor skills - Sri Widayati; Melia Dwi Widayanti; Anastasia Wardah Aulia (Atfaluna: Journal of Islamic Early Childhood Education, 2023)
Stimulating children's gross motor development requires exciting and fun activities. However, the learning model of playing while learning still needs innovation in child development. This study aims to identify the use of game-based learning based on its syntax in the learning process of jumping movements to optimize gross motor in children aged 5-6 years. This research uses a qualitative approach with descriptive methods. The research subject is a teacher who teaches children aged 5-6 in Aulia Islamic Kindergarten, Surabaya. Data collection techniques using observation. The indicators are jumped using both feet and coordination by observing jumping according to the footing picture. The data analysis technique used data reduction, presentation, and verification. The results showed that the teacher's teaching model was almost based on game-based learning syntax. There is one syntax that the teacher does not apply because it does not follow children's learning principles. Children also looked excited, happy, and able to jump. Therefore, the game-based learning model is suitable for early childhood institutions because children can stimulate gross motor skills in jumping exercises, stimulating meaningful learning. Subsequent research could investigate the long-term effects of diverse game-based learning models on retaining children's gross motor skills across different age groups and abilities.